UJI DAYA BUNUH ABATE BERDASARKAN DOSIS DAN WAKTU TERHADAP KEMATIAN LARVA NYAMUK Aedes sp DAN Culex sp - Suparyati Suparyati (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2020)
Dengue Hemorrhagic Fever (DHF) is an acute febrile disease caused by four viruses serotypes from Flafivirus, it is RNA virus from the Flaviviridae family. Dengue is transmitted by the Aedes sp. Culex sp. is a mosquito that become a filariasis (elephantiasis) vector. Both of these diseases are transmitted to humans through mosquito bites. The insecticides as larvacides likes abate or temephos is generally use by the community in Indonesia to control these vectors.The purpose of this study was to determine the most effective doses and time duration needed by abate to kill the Aedes sp and Culex sp. larvae and find out whether there was an effect of different types of Aedes sp. and Culex sp. larvae on abate’s lethality.The research method is an experiment that using 60 Aedes sp. larvae and 60 Culex sp. larvae tested with different abate doses of 8 mg, 10 mg and 12 mg using clean water.The results showed that abate at a dose of 8 mg was lethal to Aedes sp. larvae in 60 minutes and to Culex sp. larvae in 45 minutes. There is difference about abate’s ability to kill Aedes sp. and Culex sp. larvae. The conclusion is the abate’s lethality dose to Aedes sp. and Culex sp. larvae at 8 mg, 10 mg and 12 mg in 100 ml water with different times for each doses (10 mg / 100 ml water is the dose recommended by the government), abate’s lethality power to kill Aedes sp. larvae was longer than Culex sp. larvae.